The Effect of Culture on Human Bone Marrow Mesenchymal Stem Cells: Focus on DNA Methylation Profiles - Angela Bentivegna; Gaia Roversi; Gabriele Riva; Laura Paoletta; Serena Redaelli; Mariarosaria Miloso; Giovanni Tredici; Leda Dalprà (Hindawi Limited, 2016)
Human bone marrow mesenchymal stem cells (hBM-MSCs) are the best characterized multipotent adult stem cells. Their self-renewal capacity, multilineage differentiation potential, and immunomodulatory properties have indicated that they can be used in many clinical therapies. In a previous work we studied the DNA methylation levels of hBM-MSC genomic DNA in order to delineate a kind of methylation signature specific for early and late passages of culture. In the present work we focused on the modification of the methylation profiles of the X chromosome and imprinted loci, as sites expected to be more stable than whole genome. We propose a model where cultured hBM-MSCs undergo random modifications at the methylation level of most CGIs, nevertheless reflecting the original methylation status. We also pointed out global genome-wide demethylation connected to the long-term culture and senescence. Modification at CGIs promoters of specific genes could be related to the decrease in adipogenic differentiation potential. In conclusion, we showed important changes in CGIs methylation due to long-term in vitro culture that may affect the differentiation potential of hBM-MSCs. Therefore it is necessary to optimize the experimental conditions for in vitro expansion in order to minimize these epigenetic changes and to standardize safer procedures.